2018
DOI: 10.1159/000491807
|View full text |Cite
|
Sign up to set email alerts
|

The Unexpected Effects of L-Carnitine Supplementation on Lipid Metabolism in Hemodialysis Patients

Abstract: Background/Aims: There is a growing body of evidence that the long-term hemodialysis (HD) treatment leads to disturbances of carnitine homeostasis but the results of L-carnitine supplementation in HD patients have been conflicting. In the present prospective study, we investigated the effectiveness of intravenous L-carnitine in mitigating dialysis-related protein-energy wasting (PEW) based on pre-treatment albumin levels. Methods: Fifty patients (46% male, mean age 63±18.28 years, HD vintage 37.5 (7-288) month… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 28 publications
3
11
0
Order By: Relevance
“…The study indicated a significant effect of C0 supplement (1500 mg/d) on lowering serum levels of TG, TC, and LDL in atherosclerosis patients [ 32 ]. Our study reported that serum C0 concentration was negatively correlated with FBG, LDL, TG, TC, and HCY and positively correlated with HDL especially in the GDM group, which is consistent with previous researches [ 33 ]. In Nowak et al's study, C0 showed no association with insulin resistance during OGTT, and C10 and C12 decreased during OGTT with worse insulin resistance as well [ 34 ].…”
Section: Discussionsupporting
confidence: 93%
“…The study indicated a significant effect of C0 supplement (1500 mg/d) on lowering serum levels of TG, TC, and LDL in atherosclerosis patients [ 32 ]. Our study reported that serum C0 concentration was negatively correlated with FBG, LDL, TG, TC, and HCY and positively correlated with HDL especially in the GDM group, which is consistent with previous researches [ 33 ]. In Nowak et al's study, C0 showed no association with insulin resistance during OGTT, and C10 and C12 decreased during OGTT with worse insulin resistance as well [ 34 ].…”
Section: Discussionsupporting
confidence: 93%
“…Levocarnitine has also been shown to impact insulin sensitivity and protein catabolism; it has been proposed that increased levocarnitine is likely to improve nutritional status by reducing insulin resistance [160]. In one study, when patients were divided into two groups according to albumin level (<3.5 g/dL or ≥3.5 g/dL) before levocarnitine treatment, the higher albumin group displayed a significant increase in the prealbumin level and an improved malnutrition-inflammation score (MIS) [161]. Some clinical trials have indicated that levocarnitine supplementation can improve nutritional status in hemodialysis patients.…”
Section: Plasma Lipid Profiles and Inflammation-related Parametersmentioning
confidence: 99%
“…Several studies have examined the effects of levocarnitine treatment on plasma lipid levels and inflammation-related parameters in patients on maintenance dialysis. These studies are listed inTable 4 [48,80,85,86,88,90,92,[131][132][133]161,[163][164][165][166][167][168][169][170][171][172][173].…”
Section: Plasma Lipid Profiles and Inflammation-related Parametersmentioning
confidence: 99%
“…During HD, BP was measured using an electronic sphygmomanometer at several timepoints, as follows: HD initiation, initiation of BV monitoring (10 min after HD initiation; BP baseline), and hourly during HD. IDH was defined as a reduction in systolic BP ≥20 mmHg from the baseline value [17][18][19]. The interventions for symptomatic IDH, which is accompanied with nausea, dizziness, and cramps, included prompt change of the dialysis bed (Trendelenburg position), oxygen inhalation, and infusion of saline.…”
Section: Definitionsmentioning
confidence: 99%